A Genetic Algorithm for Minimum Set Covering Problem in Reliable and Efficient Wireless Sensor Networks - Attea, Bara’a; Hameed, Sarab (Iraqi Journal of Science, 2023)
Densely deployment of sensors is generally employed in wireless sensor networks (WSNs) to ensure energy-efficient covering of a target area. Many sensors scheduling techniques have been recently proposed for designing such energy-efficient WSNs. Sensors scheduling has been modeled, in the literature, as a generalization of minimum set covering problem (MSCP) problem. MSCP is a well-known NP-hard optimization problem used to model a large range of problems arising from scheduling, manufacturing, service planning, information retrieval, etc. In this paper, the MSCP is modeled to design an energy-efficient wireless sensor networks (WSNs) that can reliably cover a target area. Unlike other attempts in the literature, which consider only a simple disk sensing model, this paper addresses the problem of scheduling the minimum number of sensors (i.e., finding the minimum set cover) while considering a more realistic sensing model to handle uncertainty into the sensors’ target-coverage reliability. The paper investigates the development of a genetic algorithm (GA) whose main ingredient is to maintain scheduling of a minimum number of sensors and thus to support energy-efficient WSNs. With the aid of the remaining unassigned sensors, the reliability of the generated set cover provided by the GA, can further be enhanced by a post-heuristic step. Performance evaluations on solution quality in terms of both sensor cost and coverage reliability are measured through extensive simulations, showing the impact of number of targets, sensor density and sensing radius.